ANALISIS DESKRIPTIF TEORI PEMEROLEHAN BAHASA KEDUA - Dailatus Syamsiyah (STAI Masjid Syuhada Yogyakarta, 2017)
The Second Language Acquisition (SLA) is quite difference with the Second Language Learning (SLL). Krashen said that SLA refers to linguistic competence and focuse on linguistic forms which are naturally internalized into the learner. Instead the SLL has an opposite meaning, it is a nurture learning and a result of formal learning situation. The context of SLA is natural while the SLL is formally programmed. Usually people learn language for the sake of achievement motivation, inspite of acquiring language as a communication motivation. SLL focuse on mastering the rules of language while SLA trying to master the skill of communication. This study aims to describe the theories of second language acquisition developed by psychologists as well as linguists such as B.F. Skinner, Noam Chomsky and Stephen D Krashen. These three will give us such wide insight about an empirical concrete aspect as well as an abstract intuitive aspect of second language acquisition.